Comparison of practical application steps of the previously used adrenaline auto injector in Turkey (EpiPen) and the currently available adrenaline auto injector (Penepin): a multi-center study - Topal, Erdem (Turk Pediatri Ars, 2018)
AIM: It has been shown by a great number of studies that the correct use of adrenaline auto injectors prescribed to patients with anaphylaxis is associated with the design of the auto injector, in addition to training. The aim of this study was to compare the skills of adults in using two different auto injectors prescribed to patients with anaphylaxis. MATERIAL AND METHODS: Parents of patients aged between 1 and 18 years who referred to allergy outpatients were included in the study. RESULTS: A total of 630 volunteers from nine centers were included in the study. Four hundred fifty-seven (72.5%) of the participants were females and 235 (37.3%) were undergraduates. The rate of showing all the steps of auto injector trainers correctly by the participants was found as (60.2%) (n=379) for EpiPen and 42.9% (n=270) for Penepin (p<0.001). The most frequent mistake with both auto injector trainers was the step of “place appropriate injection tip into outer thigh/press the trigger so it clicks.” When the preferences of the volunteers were asked after training and application, 527 (83.7%) chose EpiPen, stating that it was easier and simpler to use. CONCLUSIONS: Our study showed that the correct usage rates of both adrenaline auto injectors were much lower than expected and there could be mistakes in the application of both. It could be appropriate to make improvements in the design of Penepin, which is still the only available adrenaline auto injector in Turkey, such that its application steps will be simpler and quicker.